Enhancing Value Co-Creation through Artificial Intelligence-Based Personalization among Generation Z Traveloka Users - Maulana Tri Adi; Inggang Perwangsa Nuralam; Wiyata Wiyata (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the effect of AI-enabled personalization on value co-creation among Generation Z users of Traveloka in Indonesia through perceived interactivity and perceived personalization. The study is important because AI-based personalization has become a key strategy in improving customer experience in the online travel agency (OTA) industry. Design/methodology/approach – This study used a quantitative explanatory approach with survey data collected from 200 Generation Z users of Traveloka. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Finding/Results – The results show that AI-enabled personalization significantly influences perceived interactivity, perceived personalization, and value co-creation. However, perceived interactivity and perceived personalization have positive but insignificant effects on value co-creation. Originality/Value – This study extends the application of Stimulus-Organism-Response (SOR) theory in the OTA context by highlighting the important role of AI-enabled personalization in enhancing value co-creation among Generation Z users. The findings provide practical insights for OTA companies to strengthen AI-based personalization strategies in digital services.